Πg - Locally Closed Sets And Πgl-Continuous Functions - V, DHANASEKARAN.; R, SATHISHKUMAR.; M, DEVARAJAN . (Migration Letters, 2024)
In this paper, we explore the concept of generalized πg-locally closed sets and investigate their properties within the framework of ideal topological spaces. We introduce a new class of functions, namely πgl-continuous functions, by leveraging the interplay between closed sets and specific kernels. Our study delves into the intricate relationships between these novel sets and functions, shedding light on their behaviour and applicability within the realm of ideal topological spaces, through rigorous analysis, we establish fundamental properties and theorems, providing a comprehensive understanding of the generalized πg- locally closed sets and πgl-continuous functions in this context. This research contributes to the border field of topology by extending the existing knowledge base and paving the way for further exploration in this area.